WEBSITE ADMINISTRASI SIDANG SKRIPSI PADA FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS WIDYA DHARMA PONTIANAK - Caturyadi, Fabianus; Iskandar, Riyadi J.; Willay, Thommy (INTEKSIS, 2024)
The utilization of technology, especially computers, can be applied in various areas of life, including education, specifically in the administration of thesis defense at a university. The thesis defense administration at the Faculty of Information Technology, Widya Dharma University in Pontianak, still relies on a manual system. In this research, the author designs a website that assists the secretariat, students, program coordinators, and professors in conducting online thesis defense administration. During the preparation for the thesis defense, there are several administrative challenges that are often encountered, such as grade input, collection of administrative documents, and scheduling of thesis defense sessions. Therefore, the aim of this application design is to facilitate the thesis defense administration process. The application will be designed with features such as grade input, upload of administrative documents, scheduling of defense sessions, addition of user data, addition of student information related to the thesis, confirmation of grades and submitted documents by students, and viewing of thesis defense schedules. The results of this research are expected to provide a positive contribution to improving the efficiency and effectiveness of the thesis defense administration at the Faculty of Information Technology, Widya Dharma University in Pontianak. Keywords: Web, thesis, administration.